Analysis of Volatile Flavor Substances in Commercial Soybean Paste Based on HS-SPME-GC-MS Combined with Multivariate Statistics - Jinhui JIANG; Guoyang PAN; Xinyu TAO; Ye TIAN; Feiyu AN; Yaqi WANG; Li DENG; Xing TONG; Junrui WU; Rina WU (Shipin gongye ke-ji)
To investigate the aroma differences among various soybean pastes, 33 types of soybean pastes from China were selected as the study subjects. Both aroma sensory evaluations and physicochemical indices were measured. Through factor analysis using SPSS software, 15 high-quality soybean pastes were identified for further analysis. The volatile flavor compounds in these selected pastes were analyzed using the headspace solid-phase microextraction combined with Gas Chromatography-Mass Spectrometry techniques. Multivariate statistical methods, including cluster analysis, were employed to compare the aroma similarities and differences among the various soybean pastes. The findings revealed that the 15 soybean pastes could be categorized into three groups: A, B, and C, with a total of 390 volatile flavor compounds were detected. Partial least squares discriminant analysis identified 50 distinct flavor metabolites with a VIP value greater than 1, with esters being the most prevalent, potentially contributing significantly to the aroma of soybean pastes. Notably, group C exhibited the highest total volatile flavor substance content, ranging from 197.695 to 307.785 ng/g, indicating greater aroma diversity compared to groups A and B. Among the three groups, 48 volatile flavor substances were identified, including 3-methylthiopropanal, ethyl benzoate, and benzoin aldehyde. Group C soybean pastes were found to have notably high levels of 3-methylthiopropanaldehyde, ethyl oleate, and other sauce flavored substances, as well as pleasant aroma components such as 1-octene-3-ol, 2-methyl-1-butanol, ethyl phenylacetate, and furfural, leading to their highest aroma sensory score. These substances are likely critical in shaping the aroma profile of soybean pastes. This research lays the groundwork for further exploration into the flavor quality of soybean pastes in China.